Entangled quantum Stirling heat engine based on two particles Heisenberg model with Dzyaloshinskii-Moriya interaction - Rastegar-Sedehi, H. R.; Cruz, Clebson (Frontiers in Physics, 2025)
Quantum heat engines have attracted significant attention in recent years due to their potential to surpass classical thermodynamic limits by leveraging quantum effects such as entanglement and coherence. In this study, we analyze a quantum Stirling heat engine characterized by a working substance composed of a two-particle Heisenberg model with Dzyaloshinskii–Moriya (DM) interaction under an external magnetic field. We investigate the impact of the antisymmetric interaction on the engine’s efficiency across varying coupling parameters. Our findings demonstrate that the utilization of a two-qubit Heisenberg model in an entangled quantum Stirling heat engine can significantly enhance efficiency and performance. By optimizing the antisymmetric exchange parameters, we achieve substantial enhancements in engine efficiency, with results demonstrating that the efficiency attains remarkably high values compared to other cycles utilizing the same working substance. These enhancements are primarily influenced by the DM interaction and the entangled states of the working substance, leading to superior performance.